Pensamento algébrico no currículo do ciclo de alfabetização: estudo comparativo de duas propostas - Lima, José Roberto de Campos (2018)
In this paper, we present a qualitative research guided by the goal of investigating what the approach given to algebraic thinking in the prescribed curriculum of literacy cycle, which refers to the first three years of elementary school (children from 6 to 8 years old) of two proposals. To this end, we seek to characterize elements of algebraic thinking implicit or explicit in two documents, one of the federal sphere, the National Curricular Common Base (NCCB), and other of the state sphere, the Math Curriculum Guidelines for the Early Years (MCGEY). The NCCB was chosen because it is a document in the implementation phase, which every Brazilian education networks have as a reference for the elaboration of their own curriculum and, in the case of MCGEY, the state of São Paulo has the largest number of enrolments in literacy cycle. In addition, its curriculum is used by a large number of municipalities in the state. Thus, we decided to perform a documental analysis, in which the data collection occurred through content analysis, according to Bardin. We used the usual analytical techniques divided into three phases: pre-analysis, exploration of the material and processing of results, in which, through a “floating reading”, we refined the content until we get a material that met our goal. After this reading, investing in the observation, we established three categories for analysis, one that observes the structure with which the documents were elaborated; another to examine evidences of approach given to the algebraic thinking in different axes or thematic units of math; and, finally, the conceptual, which points to possible concepts involving algebraic thinking, either explicitly or implicitly. By analying the documents, in the NCCB, we identified a conceptual approach to the research area called Early Algebra, which has as its premise the possibility of developing algebraic thinking since the early years of schooling and not just from the final years of primary school, as Lins and Gimenez already pointed out. In MCGEY, we have evidences that can lead to the development of algebraic thinking, but in an implicity way, so this kind of mathematical thinking is hardly mentioned. The algebraic thinking in the literacy cycle is presented as identification, understanding of patterns and regularities in various contexts that can be generalized, without the need for a symbolic algebraic language. Therefore, it was necessary to understand how algebra interacts with other subareas of mathematics. We consider that it is very important to understand the development of algebraic thinking in the prescribed curriculum, both for initial and continuing training of teachers and for the preparation of materials and curricular structures, as well as a possibility that contributes to the mathematical training of students